DETERMINATION OF DOPAMINE AND SEROTONIN WITH IMMUNE STATE CD4 AND CD8 OF THE NEWCASTLE INFECTION IN BROILERS - Amjed. H. Ulaiwi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to describ the course of Newcastle disease at 24 and 72 hr. of infections in broilers flocks within the period (1-December-2021 to 1- Jun- 2022) and the study aimed to determine the immunological (CD4, CD8) response and changes in neurotransmitter hormones. The blood samples were collected and prepared then examined by ELISA kits test and were worked under the protocols of companies. The result of immunological response showed the response to cellular immunity (CD8) in all cases increasing within 24hr.with statistically represented levels while, the result of humoral immunity (CD4) increasing in all cases except two cases within 72hr. with statistically significant levels as well as the results of (CD4/ CD8) ratio. while the results neurotransmitter hormones concentration revealed all cases statistically decreased represented levels at 72hr. The study concluded the 1st immune response within 24hr. showed elevation with cellular immunity then humoral immunity after 48-72hr. Also the ND infections caused down-regulation of neurotransmitter hormones by decreasing to serotonin and dopamine levels during all periods of infections.